Integrating Gravity and Surface Elevation With Magnetic Data: Mapping the Curie Temperature Beneath the British Isles and Surrounding Areas - Baykiev, Eldar; Guerri, Mattia; Fullea, Javier (Frontiers in Earth Science, 2018)
In this work, we study the lithospheric structure of the British Isles using a methodology that allows for forward modelling of the Curie temperature depth based on seismic, elevation and gravity observations within an integrated geophysical-petrological approach (LitMod3D). We compute 3D thermal models and self-consistently determine the density in the mantle based on temperature, pressure and bulk composition. Finally, we derive Curie temperature depth maps and forward calculate magnetic anomalies at the airborne level using a spherical magnetic modelling software (magnetic tesseroids) to estimate the geothermal magnetic signal. Our results show lateral lithospheric variations across the model domain, with Great Britain being characterized in general by thicker and colder lithosphere, especially in the south-east, and the thinnest and warmest lithosphere being located beneath west Scotland, Northern Ireland and in the north-west oceanic area. Our estimated Curie temperature depth map resembles the values obtained using other techniques (spectral method and surface heat flow inversion) in some areas, but discrepancies are notable in general. We determine that the effect of typical lateral temperature variations (i.e., Curie isotherm depth) accounts for 5-15%, on average, and up to 70% locally of the crustal magnetic signal at the airborne level (5 km altitude). Our lithospheric models are in general agreement with published tomography models as well as other geophysical studies.